ISLAMIC DA'WAH BROADCASTING METHOD ON ISMAIL RADIO 774 AM PONDOK GEDE BEKASI - Ujang Habibi; Alwan Faisal Rosyad (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2022)
Research purpose: How the Islamic Da'wah Broadcasting method on the Ismail Radio 774 AM. Conclusion: Two methods applied by Ismail Radio774 AM. The first is the adlibitum method, namely the method of delivering broadcasts through conversation, relaxed. Broadcasters do so without text or script by using fluent, clear, firm and uncomplicated speech. The scond method is script reading, the method is a broadcast while reading the text, either the text is made by yourself or someone else's. In this case, the reading of the text needs to be done as if you are not reading a script, as if it was read ad libitum without a tone of reading.